1960
DOI: 10.1037/h0047654
|View full text |Cite
|
Sign up to set email alerts
|

The effect of a course in psychology on the attitudes of research and development supervisors.

Abstract: In comparing lecture and nondirective approaches to changing group attitudes, 72 corporation supervisors taking a psychology course were subjected to pre and posttest comparisons of attitudes toward the supervisory role using a sentence completion test with both experimental and control groups. Negative findings involving a worsening of attitudes in the control group was attributed to group solidarity stimulated by threat of competition being forced upon them from without. The lecture method and emphasis on re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
7
0

Year Published

1968
1968
2015
2015

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…A limitation of goal‐setting theory is its exclusive focus on conscious motivation (Latham & Locke, ). Regarding future directions for motivation research, Locke and Latham (, p. 395) specifically called for studies on “subconscious as well as conscious motivation and the relationship between them.” Similarly, Miner (, ) argued that the study of organizational behavior would remain incomplete until subconscious processes are understood. Thus, we examined the effects of both consciously set and primed fairness goals.…”
Section: Removing Roadblocks To Fairnessmentioning
confidence: 99%
“…A limitation of goal‐setting theory is its exclusive focus on conscious motivation (Latham & Locke, ). Regarding future directions for motivation research, Locke and Latham (, p. 395) specifically called for studies on “subconscious as well as conscious motivation and the relationship between them.” Similarly, Miner (, ) argued that the study of organizational behavior would remain incomplete until subconscious processes are understood. Thus, we examined the effects of both consciously set and primed fairness goals.…”
Section: Removing Roadblocks To Fairnessmentioning
confidence: 99%
“…Related research has demonstrated that motivation of this kind can be increased as a result of the mediation of management development procedures (Miner, 1960(Miner, , 1961(Miner, , 1963(Miner, , 1965a(Miner, , 1965b.…”
mentioning
confidence: 97%
“…I N A series of studies extending over a nwnber of years, a relationship between managerial motivation as measured by the Miner Sentence Completion Scale (MSCS) and managerial success has emerged with rather surprising consistency. Related research has demonstrated that motivation of this kind can be increased as a result of the mediation of management development procedures (Miner, 1960(Miner, , 1961(Miner, , 1963(Miner, , 1965a(Miner, , 1965b.…”
mentioning
confidence: 99%
“…As he did with knowledge tests, Canter found that trained personnel showed significant improvement in mean attitude scores in comparison with an untrained control group. Miner (1960) conducted a lecture course specifically designed to foster more favorable attitudes toward the supervisory role. The course consisted of 10 1/2-hour sessions at weekly intervals.…”
Section: Change Of Attitudes and Self-insightmentioning
confidence: 99%